Since a day reading Balzac: novel/ feuilleton on foundational fiction by Alberto Blest Gana (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Alberto Blest Gana, the founder of the Chilean novel, could not be linked to the practice of writing feuilleton, although a number of his works published in magazines and newspapers exist. Moreover, being an outstanding disciple of Balzac would unlikely link him to the popular or mass literature, as the one developed in France in the middle of the nineteenth century. In fact, the national literary canon is built upon an intellectual elite —enlightened and liberal— that participates in the social construction of the nation as the one fostered by José Victorino Lastarria and Blest Gana —in their respective literary manifests. In their view, the popular culture does not participate beyond a folkloric ―costumbrism‖ or as a local ―taste‖, or as a ―picturesque trait‖ for the delight of the educated readers. For this reason, this article explores the melodramatic formants in Blest Gana‘s narrative, by analyzing them in light of the popular literature perspectives advocated by Eco (1981, 2012), Martín-Barbero (2010), Herlinghaus (2002), and Sarlo (1985), among others.
Keywords: Chilean literature of the XIXth Century; Feuilleton; Foundational fictions